Implementasi Nilai-Nilai Pancasila dalam Lingkungan Sekolah - Mindyasningrum, Mieke (Faculty of Teacher Training and Education of Undaris, 2024)
Education is an important instituation in educating the nation’s generation. However, education in Indonesia is still not advanced, there are many factors that cause education to not progress. Namely the lack of application of the values in Pancasila which is the gulding ideology in Indonesia. These values are still not applied to students who will ultimately become members of society who blend in various fields of life. Pancasila values are increasingly being eroded by the number of foreign cultures that are not properly filtered. Until now, Pancasila has only been memorized but not implemented properly and corrctly. So, as educators in educational institutions, ou must apply Pancasila values to students to advance education in IndonesiaKeywords: Implementation, Pancasila, Education